Insulin dose adjustments with add-on glucagon-like peptide-1 receptor (GLP-1R) agonists in clinical practice. (July 2015) - Artigas, Carla Francés; Stokes, Victoria; Tan, Garry D; Theodorakis, Michael J
<x xml:space="preserve">Abstract</x> Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are gaining ground as therapeutic modalities in combination with insulin in patients with type 2 diabetes mellitus. Exploiting the multiple benefits of incretin-based therapies in certain patient populations, especially in those who would benefit most from potential weight loss or prevention of body weight gain, has provided a valuable add-on option in diabetes management. However, caution needs to be exercised when initiating such a double injectable therapy, as evidence indicates that, in most instances, the insulin dose needs to be re-adjusted. The majority of published studies suggest reduction of insulin dose, especially related to the 'bolus' component; however, some have also recommended that insulin dose should actually be increased, but we found no credible evidence to support the latter. An important determinant of the titration process is the insulin formulation already in use at baseline. As more potent and long-acting GLP-1RAs are introduced, optimal insulin dose scaling is a major challenge, especially in a primary setting. We provide an overview of the current knowledge in this rapidly changing field. Based on currently reported evidence, a reduction of basal insulin by 10% and a decrease of prandial insulin by 30 – 40% is recommended on addition of GLP-1RAs.